2014
DOI: 10.3109/14764172.2014.946048
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of dermal filler complications in the perioral region

Abstract: Complications of oral region fillers are similar in clinical presentation but differ in etiology, therefore necessitating different clinical approaches. Imaging techniques add useful information for treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 22 publications
0
46
0
Order By: Relevance
“…Unfortunately, they did not address this diversity in their work. The study by Grippaudo et al confirmed the utility of MRI in differentiating between granulomas and fibrosis . On the other hand, Di Girolamo et al showed a statistically significant difference between various granulomas in contrast enhancement during MRI.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Unfortunately, they did not address this diversity in their work. The study by Grippaudo et al confirmed the utility of MRI in differentiating between granulomas and fibrosis . On the other hand, Di Girolamo et al showed a statistically significant difference between various granulomas in contrast enhancement during MRI.…”
Section: Discussionmentioning
confidence: 91%
“…The attempts to image dermal filler deposits using the magnetic resonance imaging (MRI) and computed tomography (CT) showed the utility of both methods for specifying the location of the previously administered dermal filler . Ginat and Schatz presented CT and MR images of various dermal fillers and their chronic complications, such as abscesses, overcorrection, migration, chronic inflammation, scarring and foreign body granulomas .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal therapy for complications to dermal fillers depends on the nature, the onset of the complication, and the type of injected substance. A variety of therapeutic regimes have been suggested in the literature, including antibiotics, hyaluronidase, local or systemic corticosteroids, antimalarial drugs (mainly hydroxychloroquine), antihistamine, surgical excision, and laser treatment [11]. The first stage in the therapy is to identify the dermal filler given.…”
Section: Discussionmentioning
confidence: 99%